2004
DOI: 10.1016/j.virusres.2004.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and budding of influenza virus

Abstract: Influenza viruses are causative agents of an acute febrile respiratory disease called influenza (commonly known as "flu") and belong to the Orthomyxoviridae family. These viruses possess segmented, negative stranded RNA genomes (vRNA) and are enveloped, usually spherical and bud from the plasma membrane (more specifically, the apical plasma membrane of polarized epithelial cells). Complete virus particles, therefore, are not found inside infected cells. Virus particles consist of three major subviral component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
263
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(274 citation statements)
references
References 182 publications
(263 reference statements)
7
263
0
4
Order By: Relevance
“…The present observations afford insight into the molecular architecture of influenza virions, whose diverse forms represent the outcome of complex patterns of interactions among viral components: the glycoproteins, matrix protein, and the RNPs; and host factors (15). Because different viral strains propagated in the same cells produce different distributions of virion shapes (e.g., elongated vs. spherical), it follows that plasticity in the interactions among viral components is a major contributor to pleiomorphy.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The present observations afford insight into the molecular architecture of influenza virions, whose diverse forms represent the outcome of complex patterns of interactions among viral components: the glycoproteins, matrix protein, and the RNPs; and host factors (15). Because different viral strains propagated in the same cells produce different distributions of virion shapes (e.g., elongated vs. spherical), it follows that plasticity in the interactions among viral components is a major contributor to pleiomorphy.…”
Section: Discussionmentioning
confidence: 80%
“…In this process, the glycoproteins accumulate in lipid rafts, where they interact with the underlying matrix protein. Host factors also participate, particularly in the final stage of pinching off (15). During assembly, a dilemma common to all viruses with segmented genomes must be resolved: how to assign the various segments appropriately to nascent virions?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study [3] demonstrated that actin is not essential for vRNP transport as IFV replication was not affected by disruption of actin polymerization. In addition, there is evidence that vRNPs may be are transported to the plasma membrane through association with the cytoplasmic tails of HA and NA [24]. This latter ''piggy-backing'' transport mechanism is not mutually exclusive with transport in association with the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…There, host replication machinery is coopted to produce viral RNA and protein that are packaged into new viral particles and transported to the cell surface (16). Neuraminidase cleaves the sialic acid link between the viral HA and cell surface glycans that tether the virus to the host cell, liberating viral progeny to perpetuate the infectious cycle (17,18).…”
mentioning
confidence: 99%